Structure and Elemental Composition of Pb1 – xSnxS Films - P.V. Koval; А.S. Оpanasyuk; A.I. Turavets; I.S. Tashlykov; A.A. Ponomarev; P. Zhukowski (Журнал нано- та електронної фізики)
In this paper by the methods of diffractometry, scanning and atomic force microscopy, X-ray characteristic radiation induced by focused proton beam (PIXE), Rutherford backscattering of helium-4 ions we have investigated Pb1 – xSnxS films obtained by "hot wall". It was found that layers obtained by condensation in the temperature range of Ts = (268-382) °C have virtually a single phase orthorhombic crystal structure with lattice parameters which vary in the range of a = (0.4214-0.4293) nm, b = (1.1246-1.1313) nm, c = (0.3980-0.4015) nm. CSD sizes in the films are equal to L(040) = (35.5-47.5) nm, L(131) = (44.4-51.5) nm. The distribution of the components of a compound of films (μ-PIXE) and their elemental composition (PIXE) are determined. It was found that some samples were depleted by sulfur in comparison with the stoichiometric composition. Atomic concentration of the components of the solid solution varies in the range of СPb = 12.71-19.13; CSn = 40.29-44.46; CS = 38.36-42.75 at. %. By increasing the substrate temperature, the lead content in the films increases and the sulfur content decreases, the atomic concentration of tin in this case varies slightly.